Composite electrolyte of multilayer structure and secondary battery using same

By adopting multi-layer composite electrolytes in secondary batteries and using different combinations of polymers and ceramic materials, the problems of flammable and explosive liquid electrolytes and low conductivity of solid electrolytes are solved, achieving efficient electrochemical performance and wearability.

CN119542514APending Publication Date: 2025-02-28SEVEN KING ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411936450.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-03-28
Filing Date
2018-03-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The liquid electrolyte used in existing secondary batteries is flammable and explosive at impact and high temperatures, and the solid electrolyte is low in ionic conductivity and high interface resistance at room temperature, making it difficult to meet the electrochemical characteristics of the positive and negative electrodes at the same time.

Method used

Using a multi-layer structure composite electrolyte, a composite electrolyte layer with excellent stability and electrochemical characteristics is prepared by adding a small amount of liquid electrolyte to the mixture of polymer and ceramic materials. The composite electrolyte layer uses different combinations of polymers and ceramics in the positive electrode and negative electrode, respectively, to meet their respective characteristic needs.

Benefits of technology

It achieves high ionic conductivity, low interface resistance and excellent thermal stability, can meet the electrochemical characteristics requirements of both the positive and negative electrodes, extends the cycle life of the battery, and the battery itself can be bent freely, suitable for wearable products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542514A_ABST
    Figure CN119542514A_ABST
Patent Text Reader

Abstract

The present invention relates to a multilayer structure composite electrolyte for a secondary battery and a secondary battery using the same. The multilayer structure composite electrolyte according to the present invention is obtained by laminating two or more layers of a composite electrolyte containing a small amount of a liquid electrolyte in a mixture of a polymer and a ceramic material. The multilayer structure composite electrolyte has the same stability as a solid electrolyte, and has the same or more excellent electrochemical characteristics as a liquid electrolyte. The multi-layer structure composite electrolyte can be folded at will, and therefore the multi-layer structure composite electrolyte can also be used in wearable devices.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the Chinese patent application with application number 201880022153.2, application date March 19, 2018, and invention name “Multilayer structured composite electrolyte and secondary battery using the same”. Technical Field

[0002] The present invention relates to a multilayer composite electrolyte for a secondary battery and a secondary battery using the same. The multilayer composite electrolyte of the present invention is prepared by laminating two or more layers of a composite electrolyte containing a small amount of liquid electrolyte in a mixture of a polymer and a ceramic material. The multilayer composite electrolyte of the present invention has the same stability as a solid electrolyte and has the same or better electrochemical properties as a liquid electrolyte. In addition, the multilayer composite electrolyte of the present invention can be folded arbitrarily, so it can also be used in wearable devices. Background Art

[0003] The application fields of secondary batteries are expanding day by day, and they can not only charge and discharge portable devices such as mobile phones, laptops, and cameras, but also charge and discharge electric vehicles. Generally, secondary batteries are composed of a positive electrode, a negative electrode, an electrolyte located therebetween, and a polymer separator.

[0004] At present, the most commonly used secondary battery is a lithium-ion secondary battery. Lithium-ion secondary batteries use liquid electrolytes, especially ion-conductive organic liquid electrolytes that are made by dissolving salts in non-aqueous organic solvents. However, liquid electrolytes are inherently weak to heat and shock, and are highly flammable. Therefore, lithium-ion secondary batteries have the problem of exploding or burning when they are damaged by external impact or when the temperature of the secondary battery rises.

[0005] In order to solve such a problem, efforts have been made to replace liquid electrolytes with solid electrolytes such as ceramic solid electrolytes and polymer electrolytes. However, although these solid electrolytes have high stability, they have low ionic conductivity at room temperature and high interface resistance with electrodes, thereby having other problems that reduce the electrochemical characteristics of secondary batteries.

[0006] In order to solve these problems of solid electrolytes, attempts have been made to prepare solid composite electrolytes by mixing ceramic materials with polymers and adding a small amount of liquid electrolytes therein. The composite electrolytes prepared in this way not only improve thermal stability, but also reduce interface resistance, and contain lithium ion-activated ceramics, thereby improving the movement of lithium ions and further improving electrochemical properties.

[0007] However, since the positive electrode and the negative electrode of a secondary battery have different electrochemical reactions and require different electrochemical characteristics, it is difficult to find optimal polymers or ceramics for both the positive electrode and the negative electrode. Summary of the invention

[0008] Problems to be solved by the invention

[0009] The present invention provides a composite electrolyte with a multilayer structure and a secondary battery using the same in order to solve the existing problems of composite electrolytes. The secondary battery uses a composite electrolyte layer of a polymer and ceramic suitable for the positive electrode portion in the positive electrode portion, and a composite electrolyte layer of a polymer and ceramic suitable for the negative electrode portion in the negative electrode portion. Specifically, the performance of the composite electrolyte is improved by specifically disclosing a combination of a polymer and ceramic suitable for the positive electrode portion and the negative electrode portion.

[0010] Solutions for solving problems

[0011] The composite electrolyte for secondary batteries with a multilayer structure of the present invention is a composite electrolyte for secondary batteries, characterized in that it comprises: a first composite electrolyte layer arranged toward the positive electrode portion; a second composite electrolyte layer arranged toward the negative electrode portion, wherein the first composite electrolyte layer and the second composite electrolyte layer respectively comprise a polymer substrate and a ceramic material different from each other. The first composite electrolyte layer and the second composite electrolyte layer further comprise a liquid electrolyte.

[0012] The composite electrolyte for secondary batteries with a multilayer structure of the present invention may further include a single-layer or multi-layer additional electrolyte layer located between the first composite electrolyte layer and the second composite electrolyte layer. The additional electrolyte layer is characterized in that it includes a polymer substrate and a ceramic material. The additional electrolyte layer may include a liquid electrolyte.

[0013] The first composite electrolyte layer of the present invention is characterized in that it has excellent stability, reactivity, etc. in the positive electrode portion compared to the second composite electrolyte layer, and the second composite electrolyte layer is characterized in that it has excellent stability, reactivity, etc. in the negative electrode portion compared to the first composite electrolyte layer. The first composite electrolyte layer and the second composite electrolyte layer of the present invention are characterized in that they respectively contain different ceramic materials and / or different polymers.

[0014] Effects of the Invention

[0015] In the past, attempts have been made to solve the stability problem of secondary batteries using liquid electrolytes by applying solid electrolytes or composite electrolytes. Solid electrolytes are made only of polymers or ceramics, polymer electrolytes have low ionic conductivity at room temperature, and ceramic solid electrolytes have high interface resistance with electrodes. Composite electrolytes are prepared from ceramics and polymers, or by adding liquid electrolytes to ceramics and polymers, but since they are prepared only as a single layer, they cannot simultaneously meet the characteristics of the positive and negative electrodes of secondary batteries.

[0016] On the contrary, the composite electrolyte for secondary batteries having a multilayer structure of the present invention has high ion conductivity, reduces the interface resistance with the electrodes, and satisfies various characteristics required of the positive electrode and the negative electrode at the same time.

[0017] The secondary battery using the composite electrolyte having a multilayer structure of the present invention has the following advantages: excellent thermal stability, excellent capacity, and the capacity does not decrease much but remains unchanged as the charge-discharge cycle proceeds.

[0018] The secondary battery using the composite electrolyte having a multilayer structure of the present invention has the following advantages: the secondary battery itself can be bent freely, and therefore, it can also be freely applied to wearable products and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Three pathways for the movement of lithium or sodium ions in a composite solid electrolyte are shown.

[0020] Figure 2 A schematic diagram of a multilayer composite electrolyte is shown, in which a first composite electrolyte layer is prepared using LTAP (sometimes abbreviated as LTAPO) as a ceramic material, PVdF as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) as a liquid electrolyte, and a second composite electrolyte layer is prepared using LLZO as a ceramic material, PVdF as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) as a liquid electrolyte, and then the first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) are laminated to prepare the multilayer composite electrolyte.

[0021] Figure 3 Show Figure 2 Surface scanning electron microscope (SEM) image of the first composite electrolyte layer of the multi-layer composite electrolyte layer.

[0022] Figure 4 Show Figure 2 Surface SEM image of the second composite electrolyte layer of the multi-layer composite electrolyte layer.

[0023] Figure 5 Show Figure 2 Cross-sectional SEM image of the multilayer composite electrolyte.

[0024] Figure 6 Show Figure 2 Cross-sectional scanning electron microscope-energy dispersive spectrometer (SEM-EDS) elemental analysis diagram of the multilayer composite electrolyte.

[0025] Figure 7 A graph showing the discharge capacity versus the number of cycles of the secondary battery of Example 2.

[0026] Figure 8 A graph showing the discharge capacity versus the number of cycles of the secondary battery of Comparative Example 1.

[0027] Fig. 9 This figure shows the state of the first composite electrolyte layer of the secondary battery of Example 2 after 50 cycles.

[0028] Fig.10 This figure shows the state of the second composite electrolyte layer of the secondary battery of Example 2 after 50 cycles.

[0029] Fig.11 A diagram showing the state of a single composite electrolyte layer of the secondary battery of Comparative Example 1 after 50 cycles.

[0030] Fig.12 A graph showing the ionic conductivity of the electrolytes of Example 3, Comparative Example 2, and Comparative Example 3 at room temperature.

[0031] Fig.13 A graph showing the interface resistance of the electrolytes of Example 3 and Comparative Example 2.

[0032] Fig.14 Graph showing the ion conductivity of the secondary battery of Example 4 and the secondary battery of Example 2.

[0033] Fig.15 Graphs showing the results of charge and discharge tests on the secondary battery of Example 4 and the secondary battery of Example 2.

[0034] Fig.16 It is a graph showing the ionic conductivity of the secondary batteries of Examples 4-7.

[0035] Fig.17 Graphs showing the results of charge and discharge tests on the secondary batteries of Examples 4-7.

[0036] Fig.18 Graphs showing the results of charge and discharge tests on the secondary batteries of Examples 8 to 10.

[0037] Fig.19 is a graph showing the ionic conductivity of the secondary batteries of Examples 11 to 14.

[0038] Fig. 20 Graphs showing the results of charge and discharge tests on the secondary batteries of Examples 11 to 14.

[0039] Fig.21 A diagram showing ceramics, liquid electrolyte, and polymer that constitute a composite solid electrolyte. DETAILED DESCRIPTION

[0040] The composite electrolyte layer of the present invention may include ceramic material, polymer, and liquid electrolyte. When the ceramic material and the polymer are 100 weight percent, the ceramic material can be 99 weight percent to 40 weight percent, and the polymer can be 1 weight percent to 60 weight percent. The ceramic material is preferably 80 weight percent to 70 weight percent, and the polymer is preferably 20 weight percent to 30 weight percent. Relative to 100 weight parts of the ceramic material and the polymer composite, the liquid electrolyte can be 5 weight parts to 40 weight parts. Relative to 100 weight parts of the ceramic material and the polymer composite, the liquid electrolyte is preferably 10 weight parts to 20 weight parts.

[0041] The above ceramic material is a sulfide, an oxide, a phosphate or a mixture thereof. Sulfide ceramics are ceramics containing sulfur in the crystal structure, such as Li2S-P2S5, Li7P2S 11 , Li 3.25 Ge 0.25 P 0.75 S4 (LGPS), Li2S-Si2S5, Li2S-Ga2S3-GeS2, Li2S-Sb2S3-GeS2. Oxide ceramics are ceramics containing oxygen in the crystal structure, such as Al2O3, β-Al2O3, TiO2, BaTiO3, SiO2, (La, Li)TiO3 (LLTO), Li5La3Ta2O 12 、Li4SiO4Li3BO 2.5 N 0.5 Phosphate ceramics are ceramics containing phosphorus in the crystal structure, such as LAGP (Li 1+x Al x Ge 2-x (PO4)3)(O <x<2)、LTAP(Li 1+x Ti 2-x Al x (PO4)3)(0 <x<2)、Li 1+x Ti 2-x Al x Siy(PO4) 3-y (0 <x<2、0<y<3)。

[0042] The above polymers can be polyvinylidene fluoride (PVdF) and copolymers, poly(vinylidene fluoride-trifluoroethylene copolymer) and copolymers, polyethylene glycol (PEO) and copolymers, polyacrylonitrile (PAN) and copolymers, poly(methyl methacrylate) (PMMA) and copolymers, polyvinyl chloride and copolymers, polyvinyl pyrrolidone (PVP) and copolymers, polyimide (PI) and copolymers, polyethylene (PE) and copolymers, polyurethane (PU) and copolymers, polypropylene (PP) and copolymers. and copolymers, poly(propylene oxide) (PPO) and copolymers, poly(ethylene imine) (PEI) and copolymers, poly(ethylene sulfide) (PES) and copolymers, poly(vinyl acetate) (PVAc) and copolymers, poly(ethylene succinate) (PESc) and copolymers, polyesters and copolymers, polyamines and copolymers, polysulfides and copolymers, siloxane-based and copolymers, styrene butadiene rubber (SBR) and copolymers, carboxymethyl cellulose (CMC) and copolymers, their derivatives and their combinations.

[0043] The above-mentioned liquid electrolyte can be a lithium salt or a sodium salt dissolved in a non-aqueous organic solvent or an ionic liquid solvent, but is not limited thereto, and can include all types of liquid electrolytes commonly used in the art. The above-mentioned non-aqueous organic solvent can be a carbonate, an ester, an ether, a ketone, an alcohol, an aprotic solvent, or a combination thereof. The above-mentioned ionic liquid solvent is a solvent of an imidazolium, pyridinium, pyrrolidinium, sulfonium, pyrazolium, ammonium, morpholinium, phosphonium, piperidinium cation, or a combination thereof. The structure of the ionic liquid cation is as follows.

[0044]

[0045] The lithium salt used in the above-mentioned liquid electrolyte is LiClO4, LiPF6, CF3SO2NLiSO2CF3 (LiTFSI), Li[N(SO2F)2](LiFSI), Li[B(C2O4)2](LiBOB), LiAsF6, (fluorosulfonyl)(trifluoromethanesulfonyl)lithium imide (lithiumfluorosulfonyl-trifluoromethanesulfonylimide, LiFTFSI) or a combination thereof.

[0046] The sodium salts used in the above liquid electrolyte are NaClO4, NaPF4, NaPF6, NaAsF6, NaTFSI, Na[(C2F5)3PF3] (NaFAP), Na[B(C2O4)2] (NaBOB), Na[N(SO2F)2] (NaFSI), NaBeti (NaN[SO2C2F5]2), or a combination thereof.

[0047] In the above composite solid electrolyte, lithium ions or sodium ions move through the three paths described below.

[0048] (1) Movement through the contacted ceramic (pumping movement)

[0049] (2) Movement through the liquid electrolyte

[0050] (3) Movement across the ceramic material and the liquid electrolyte

[0051] Figure 1 The above three movement paths are shown. Figure 1 The meaning of each figure in Fig.21 is as shown.

[0052] The above first composite electrolyte layer can use a ceramic material with good ionic conductivity. Oxide series, phosphate series, sulfide series, etc. can be used. The better the ionic conductivity of the ceramic material used, the better the electrochemical properties. Preferably, the first composite electrolyte layer uses a ceramic material with a conductivity greater than 10 -3 S / cm. For example, LTAP (Li 1+ x Ti 2-x Al x (PO4)3) (0 < x < 2), LAGP (Li 1+x Al x Ge 2-x (PO4)3) (0 < x < 2), LLTO (Li3xLa 2 / 3-x TiO3) ((0 < x < 2 / 3) can be used as the ceramic material of the first composite electrolyte layer.

[0053] In addition, Li2S-P2S5, Li2O-SiO2, Li7La3Zr2O 12 (LLZO), Li-β-Al2O3, Li 3.25 Ge 0.25 P 0.75 S4 (LGPS) can be used as the ceramic material of the first composite electrolyte layer.

[0054] The above second composite electrolyte layer can use Al2O3, such as Li6La2BaTa2O 12, garnet of LLZO (Li7La3Zr2O 12 ), such as ceramic materials like composites (Composite) of LiX - Al2O3 (X can be I, N). The ceramic material used for the second composite electrolyte layer depends on the type of negative electrode used in the secondary battery. For example, when using lithium as the negative electrode, it is preferably not to use ceramics containing Ti, Si, S, Ge. When using graphite (carbon), silicon or germanium as the negative electrode, it is preferably not to use ceramics containing Ti, S.

[0055] In addition, β - Al2O3, Li2O - SiO2, Li 3.25 Ge 0.25 P 0.75 S4 (LGPS), LAGP (Li 1+x Al x Ge 2-x (PO4)3) (0 < x < 2) can be used as the ceramic material for the second composite electrolyte layer.

[0056] The polymers used in the above - mentioned first composite electrolyte layer are polyvinylidene fluoride (Polyvinylidenefluoride, PVdF) - based and copolymers, poly(vinylidene fluoride - trifluoroethylene copolymer) - based and copolymers, polyethylene glycol (PEO) - based and copolymers, polyacrylonitrile (PAN) - based and copolymers, poly(methyl methacrylate) (PMMA) - based and copolymers, polyvinyl chloride - based and copolymers, polyvinylpyrrolidone (PVP) - based and copolymers, polyimide (PI) - based and copolymers, polyethylene (PE) - based and copolymers, polyurethane (PU) - based and copolymers, polypropylene (PP) - based and copolymers, poly(propylene oxide) (PPO) - based and copolymers, poly(ethylene imine) (PEI) - based and copolymers, poly(ethylene sulfide) (PES) - based and copolymers, poly(vinyl acetate) (PVAc) - based and copolymers, poly(ethylene succinate) (PESc) - based and copolymers, polyester - based and copolymers, polyamine - based and copolymers, polysulfide - based and copolymers, siloxane - based (Siloxane - based) - based and copolymers, styrene - butadiene rubber (SBR) - based and copolymers, carboxymethyl cellulose (CMC) - based and copolymers, their derivatives and their combinations.

[0057] When the charging voltage is set to 4.4V or more, it is preferably to use polyvinylidene fluoride (Polyvinylidenefluoride, PVdF) - based and copolymers. In addition, it is preferably to use polyacrylonitrile (Polyacrylonitrile, PAN) - based and copolymers as the polymer of the first composite electrolyte layer.

[0058] The polymers used in the above-mentioned second composite electrolyte layer can be the same as those used in the first composite electrolyte layer. Preferably, polyacrylonitrile (PAN) - based polymers and copolymers, polyurethane (PU) - based polymers and copolymers with excellent strength and electrochemical stability are used. Additionally, styrene - butadiene rubber (SBR) - based polymers and copolymers, carboxymethyl cellulose (CMC) - based polymers and copolymers can be used as the polymers for the second composite electrolyte layer.

[0059] Polyvinylidenefluoride (PVdF) - based polymers and copolymers can be used as the polymers for the first composite electrolyte layer, ceramics selected from phosphates, oxides, sulfides, and mixtures thereof can be used as the ceramic materials, polyvinylidenefluoride (PVdF) - based polymers and copolymers can be used as the polymers for the second composite electrolyte layer, and phosphate ceramics can be used as the ceramic materials to prepare a multilayer composite electrolyte.

[0060] PVdF can be used as the polymer for the first composite electrolyte layer, and ceramics selected from LTAP (Li 1+x Ti 2-x Al x (PO4)3) (0 < x < 2), LLZO (Li7La3Zr2O 12 ), Li2S - P2S5, and mixtures thereof can be used as the ceramic materials, PVdF can be used as the polymer for the second composite electrolyte layer, and LAGP (Li 1+x Al x Ge 2-x (PO4)3) (0 < x < 2) can be used as the ceramic materials to prepare a multilayer composite electrolyte.

[0061] Polyvinylidenefluoride (PVdF) - based polymers and copolymers can be used as the polymers for the first composite electrolyte layer, ceramics selected from phosphates, oxides, sulfides, and mixtures thereof can be used as the ceramic materials, polyvinylidenefluoride (PVdF) - based polymers and copolymers can be used as the polymers for the second composite electrolyte layer, and oxide ceramics can be used as the ceramic materials to prepare a multilayer composite electrolyte.

[0062] PVdF, PVdF - TrFE (polyvinylidene fluoride - trifluoroethylene), or mixtures thereof can be used as the polymers for the first composite electrolyte layer, and ceramics selected from LTAP (Li 1+x Ti 2-x Al xCeramics in (PO4)3) (0 < x < 2), LLTO ((La, Li)TiO3), Li2S - P2S5, and their mixtures are used as ceramic materials, PVdF, PVdF - TrFE, or their mixtures are used as the polymer for the second composite electrolyte layer, and ceramics selected from Al2O3, β - Al2O3, LLZO (Li7La3Zr2O 12 ) and their mixtures are used as ceramic materials to prepare a multilayer composite electrolyte.

[0063] Polyacrylonitrile (PAN) - based and copolymers can be used as the polymer for the first composite electrolyte layer, ceramic materials selected from phosphates, oxides, sulfides, and their mixtures are used as ceramic materials, polyacrylonitrile (PAN) - based and copolymers are used as the polymer for the second composite electrolyte layer, and sulfide ceramics are used as ceramic materials to prepare a multilayer composite electrolyte.

[0064] Polyacrylonitrile (PAN) can be used as the polymer for the first composite electrolyte layer, and ceramics selected from LTAP (Li 1+ x Ti 2-x Al x (PO4)3) (0 < x < 2), LLZO (Li7La3Zr2O 12 )、Li2S - P2S5 and their mixtures are used as ceramic materials, polyacrylonitrile (PAN) is used as the polymer for the second composite electrolyte layer, and ceramics selected from LGPS (Li 3.25 Ge 0.25 P 0.75 S4), Li2O - SiO2 and their mixtures are used as ceramic materials to prepare a multilayer composite electrolyte.

[0066] Example 1

[0067] In the first composite electrolyte layer, LTAP is used as the ceramic material, PVdF is used as the polymer, and 1M LiPF6 in EC / DMC (ethylene carbonate / dimethyl carbonate, 1:1 vol) is used as the liquid electrolyte. In the second composite electrolyte layer, LLZO is used as the ceramic material, PVdF is used as the polymer, and 1M LiPF6 in EC / DMC (ethylene carbonate / dimethyl carbonate, 1:1 vol) is used as the liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) are laminated to prepare a multilayer composite electrolyte. Figure 2 A schematic diagram showing the multilayer composite electrolyte is shown.

[0068] Figure 3 A surface SEM image of the first composite electrolyte layer is shown. Figure 4 A surface SEM image of the second composite electrolyte layer is shown. Figure 5 shows a cross-sectional view of a multilayer composite electrolyte, Figure 6 An elemental analysis diagram of a cross section is shown.

[0069] like Figures 2 to 6 As shown, it can be seen that the structures of the first composite electrolyte layer and the second composite electrolyte layer are obviously different due to the different combinations of ceramic materials and polymers used.

[0070] Example 2

[0071] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 2 was prepared using O2 (lithium nickel cobalt manganese oxide (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 1 as the electrolyte.

[0072] Using LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Comparative Example 1 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the first composite electrolyte layer monolayer of Example 1 as the electrolyte.

[0073] The above two secondary batteries were tested for charge and discharge under the conditions of a charge voltage of 4.4V, a discharge voltage of 3.0V, and a battery capacity of 0.1C. Figure 7 The discharge capacity of the secondary battery of Example 2 as a function of the number of cycles is shown. Figure 8 The discharge capacity of the secondary battery of Comparative Example 1 is shown as a function of the number of cycles. The secondary battery of Example 2 has a discharge capacity of about 150 mAh / g even after 50 cycles, which is not much different from the initial discharge capacity. However, the discharge capacity of the secondary battery of Comparative Example 1 is about 110 mAh / g after 50 cycles, which is much lower than the initial discharge capacity.

[0074] Fig. 9 The state of the first composite electrolyte layer of the secondary battery of Example 2 after 50 cycles is shown.

[0075] Fig.10 The state of the second composite electrolyte layer of the secondary battery of Example 2 after 50 cycles is shown.

[0076] Fig.11 The single-layer composite electrolyte layer of the secondary battery of Comparative Example 1 is shown after 50 cycles. Fig. 9 , Fig.10As shown in FIG. 2 , the surface of the first composite electrolyte layer and the second composite electrolyte layer of the secondary battery of Example 2 did not change even after 50 cycles of charge and discharge. Fig.11 As shown, the single-layer composite electrolyte layer (LTAP) of Comparative Example 1 reacts after 50 cycles of charge and discharge, and the surface becomes black. Since the LTAP ceramic electrolyte contains Ti, a reduction reaction occurs at 1.5V. Therefore, the reaction occurs earlier than the negative electrode, causing the surface to become black and reducing the life characteristics. However, the LTAP ceramic electrolyte is suitable as a positive electrode electrolyte due to its excellent ion conductivity.

[0077] It can be seen from the above embodiments that when lithium metal is used as the negative electrode, preferably, ceramics containing Ti, Si, S, and Ge are not used in the composite electrolyte layer on the negative electrode side.

[0078] Example 3

[0079] Example 3 compares the ionic conductivity and interface resistance of the electrolyte. The multilayer composite electrolyte prepared in Example 1 (Example 3), the multilayer composite electrolyte prepared in Example 1 without a liquid electrolyte (Comparative Example 2), and the liquid electrolyte used in Example 1 (Comparative Example 3) are compared.

[0080] Fig.12 The ion conductivity of the electrolytes of Example 3, Comparative Example 2, and Comparative Example 3 at room temperature is shown. Fig.13 The interfacial resistance of the electrolytes of Example 3, Comparative Example 2, and Comparative Example 3 is shown. Fig.12 As shown, the ionic conductivity of the liquid electrolyte of Comparative Example 3 at room temperature is 2.1x10 -3 S / cm. The ionic conductivity of the multilayer composite electrolyte of Example 3 at room temperature is 7.9x10 -4 The ionic conductivity of the electrolyte of Comparative Example 2 (a multilayer composite electrolyte not containing a liquid electrolyte) at room temperature is 1.1x10 -8 S / cm. It can be seen that the composite solid electrolyte containing a liquid electrolyte exhibits an ionic conductivity similar to that of the liquid electrolyte. However, it can be seen that the composite solid electrolyte not containing a liquid electrolyte has a significantly decreased ionic conductivity compared to the composite solid electrolyte containing a liquid electrolyte.

[0081] Fig.13 The interfacial resistance of the electrolytes of Example 3 and Comparative Example 2 is shown. Fig.13As shown, the composite solid electrolyte not containing a liquid electrolyte (Comparative Example 2) shows an interface resistance of 6000Ω, and the composite solid electrolyte containing a liquid electrolyte (Example 3) shows an interface resistance of less than 1000Ω. It can be seen that if a liquid electrolyte is included in the composite electrolyte of a ceramic material and a polymer, the interface resistance is significantly reduced.

[0082] Example 4

[0083] In the first composite electrolyte layer, LTAP was used as a ceramic material, PVdF was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte, while in the second composite electrolyte layer, β-Al2O3 was used as a ceramic material, PVdF-TrFE was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) were laminated to prepare a multilayer composite electrolyte layer.

[0084] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 4 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 4 as the electrolyte. Fig.14 The ion conductivity of the secondary battery of Example 4 and the secondary battery of Example 2 is shown. The above two secondary batteries were subjected to a charge and discharge test under the conditions of a charge voltage of 4.7 V, a discharge voltage of 3.0 V, and a battery capacity of 1 C. Fig.15 The results are shown in Table 1. The ion conductivity and discharge capacity of the above two secondary batteries were compared, as shown in Table 1 below.

[0085] Table 1

[0086] Battery Ionic conductivity Discharge capacity Example 2 <![CDATA[7.9x10 -4 S / cm]]> 130.5mAh / g Example 4 <![CDATA[2.1x10 -3 S / cm]]> 155.4mAh / g

[0087] The secondary battery of Example 2 exhibits ionic conductivity and discharge capacity comparable to those of a liquid electrolyte. For the secondary battery of Example 4, β-Al2O3 used as a ceramic material for the second composite electrolyte layer has better lithium ion conductivity than LLZO used as a ceramic material for the second composite electrolyte layer of the secondary battery in Example 2, and PVdF-TrFE used as a polymer improves the movement of lithium ions as a ferroelectric polymer compared to PVdF used in the secondary battery of Example 2, so that the ionic conductivity and discharge capacity are better than those of the secondary battery of Example 2.

[0088] Example 5

[0089] In the first composite electrolyte layer, LTAP was used as a ceramic material, PVdF was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte, while in the second composite electrolyte layer, LLZO was used as a ceramic material, PVdF-TrFE was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) were laminated to prepare a multilayer composite electrolyte layer.

[0090] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 5 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 5 as the electrolyte.

[0091] Example 6

[0092] In the first composite electrolyte layer, LLTO was used as a ceramic material, PVdF was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte, while in the second composite electrolyte layer, β-Al2O3 was used as a ceramic material, PVdF-TrFE was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) were laminated to prepare a multilayer composite electrolyte layer.

[0093] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 6 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 6 as the electrolyte.

[0094] Example 7

[0095] In the first composite electrolyte layer, Li2S-P2S5 is used as a ceramic material, PVdF is used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) is used as a liquid electrolyte, while in the second composite electrolyte layer, β-Al2O3 is used as a ceramic material, PVdF-TrFE is used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) is used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) are laminated to prepare a multilayer composite electrolyte layer.

[0096] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 7 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 7 as the electrolyte.

[0097] Fig.16 The ion conductivity of the secondary batteries of Examples 4 to 7 is shown. The above four secondary batteries were subjected to a charge and discharge test under the conditions of a charge voltage of 4.7 V, a discharge voltage of 3.0 V, and a battery capacity of 1 C. Fig.17 The results are shown in Table 2. The ionic conductivity and discharge capacity of the secondary batteries of Examples 4 to 7 were compared, as shown in Table 2 below.

[0098] Table 2

[0099] Battery Ionic conductivity Discharge capacity Example 4 <![CDATA[2.1x10 -3 S / cm]]> 155.4mAh / g Example 5 <![CDATA[1.2x10 -3 S / cm]]> 144.6mAh / g Example 6 <![CDATA[1.1x10 -3 S / cm]]> 139.5mAh / g Example 7 <![CDATA[8.1x10 -4 S / cm]]> 126.4mAh / g

[0100] The secondary batteries of Examples 4-7 exhibited ionic conductivity and discharge capacity comparable to those of liquid electrolytes.

[0101] Example 8

[0102] In the first composite electrolyte layer, LTAP was used as a ceramic material, PVdF was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte, while in the second composite electrolyte layer, LAGP was used as a ceramic material, PVdF was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) were laminated to prepare a multilayer composite electrolyte layer.

[0103] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3The secondary battery of Example 8 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 8 as the electrolyte.

[0104] Example 9

[0105] In the first composite electrolyte layer, LLZO was used as a ceramic material, PVdF was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte, while in the second composite electrolyte layer, LAGP was used as a ceramic material, PVdF was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) were laminated to prepare a multilayer composite electrolyte layer.

[0106] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 9 was prepared by using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 9 as the electrolyte.

[0107] Example 10

[0108] In the first composite electrolyte layer, Li2S-P2S5 was used as a ceramic material, PVdF was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte, while in the second composite electrolyte layer, LAGP was used as a ceramic material, PVdF was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) were laminated to prepare a multilayer composite electrolyte layer.

[0109] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 10 was prepared by using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 10 as the electrolyte.

[0110] Table 3 below shows the ionic conductivity of the secondary batteries of Examples 8 to 10. For the above three secondary batteries, a charge and discharge test was performed under the conditions of a charge voltage of 4.7 V, a discharge voltage of 3.0 V, and a battery capacity of 1 C. Fig.18The results are shown in Table 3. The ionic conductivity and discharge capacity of the secondary batteries of Examples 8 to 10 were compared, as shown in Table 3 below.

[0111] Table 3

[0112] Battery Ionic conductivity Discharge capacity Example 8 <![CDATA[1.9x10 -3 S / cm]]> 149.2mAh / g Example 9 <![CDATA[1.0x10 -3 S / cm]]> 133.9mAh / g Example 10 <![CDATA[7.5x10 -4 S / cm]]> 126.4mAh / g

[0113] The secondary batteries of Examples 8 to 10 exhibited ionic conductivity and discharge capacity comparable to those of liquid electrolytes.

[0114] Embodiment 11

[0115] In the first composite electrolyte layer, LTAP was used as a ceramic material, PAN was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte, while in the second composite electrolyte layer, LGPS was used as a ceramic material, PAN was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) were laminated to prepare a multilayer composite electrolyte layer.

[0116] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 11 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 11 as the electrolyte.

[0117] Example 12

[0118] In the first composite electrolyte layer, LLZO was used as a ceramic material, PAN was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte, while in the second composite electrolyte layer, Li2O-SiO2 was used as a ceramic material, PAN was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) were laminated to prepare a multilayer composite electrolyte layer.

[0119] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 12 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 12 as the electrolyte.

[0120] Example 13

[0121] In the first composite electrolyte layer, Li2S-P2S5 is used as a ceramic material, PAN is used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) is used as a liquid electrolyte, while in the second composite electrolyte layer, LGPS is used as a ceramic material, PAN is used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) is used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) are laminated to prepare a multilayer composite electrolyte layer.

[0122] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 13 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 13 as the electrolyte.

[0123] Embodiment 14

[0124] In the first composite electrolyte layer, LTAP was used as a ceramic material, PAN was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte, while in the second composite electrolyte layer, Li2O-SiO2 was used as a ceramic material, PAN was used as a polymer, and 1M LiPF6 in EC / DMC (ethyl carbonate / dimethyl carbonate, 1:1 vol) was used as a liquid electrolyte. The first composite electrolyte layer (upper layer) and the second composite electrolyte layer (lower layer) were laminated to prepare a multilayer composite electrolyte layer.

[0125] LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The secondary battery of Example 14 was prepared using O2 (NMC, lithium nickel manganese cobalt oxide) positive electrode material as the positive electrode, lithium metal as the negative electrode, and the multilayer composite electrolyte of Example 14 as the electrolyte.

[0126] Fig.19 The ion conductivity of the secondary batteries of Examples 11 to 14 is shown. The above four secondary batteries were subjected to a charge and discharge test under the conditions of a charge voltage of 4.7 V, a discharge voltage of 3.0 V, and a battery capacity of 1 C. Fig. 20 The results are shown in Table 4. The ionic conductivity and discharge capacity of the secondary batteries of Examples 11 to 14 were compared, as shown in Table 4 below.

[0127] Table 4

[0128] Battery Ionic conductivity Discharge capacity Embodiment 11 <![CDATA[0.3x10 -4 S / cm]]> 134.1mAh / g Example 12 <![CDATA[5.6x10 -4 S / cm]]> 117.9mAh / g Example 13 <![CDATA[4.2x10 -4 S / cm]]> 106.5mAh / g Embodiment 14 <![CDATA[7.3x10 -4 S / cm]]> 125.2mAh / g

[0129] The secondary batteries of Examples 11 to 14 exhibited ionic conductivity and discharge capacity comparable to those of liquid electrolytes.

Claims

1. A double-layer composite electrolyte for a secondary battery, comprising: A first composite electrolyte layer disposed toward the positive electrode portion; A second composite electrolyte layer is provided facing the negative electrode portion, in, The first composite electrolyte layer and the second composite electrolyte layer include a polymer substrate, an ion conductive ceramic material and a liquid electrolyte. Relative to 100 weight percent of the sum of the polymer substrate and the ion conductive ceramic material, 1 weight percent to 30 weight percent of the polymer substrate is included; relative to 100 weight percent of the sum of the polymer substrate and the ion conductive ceramic material, 70 weight percent to 99 weight percent of the ion conductive ceramic material is included, The liquid electrolyte is contained in an amount of 5 to 40 parts by weight relative to 100 parts by weight of the composite of the ion conductive ceramic material and the polymer substrate, The polymer substrate of the first composite electrolyte layer is polyvinylidene fluoride or its copolymer, and the ion conductive ceramic material is an ion conductive ceramic material selected from phosphates, oxides, sulfides and mixtures thereof. The polymer substrate of the second composite electrolyte layer is polyvinylidene fluoride or its copolymer, and the ion conductive ceramic material is a phosphate ion conductive ceramic material.

2. A double-layer composite electrolyte for a secondary battery, comprising: A first composite electrolyte layer disposed toward the positive electrode portion; A second composite electrolyte layer is provided facing the negative electrode portion, in, The first composite electrolyte layer and the second composite electrolyte layer include a polymer substrate, an ion conductive ceramic material and a liquid electrolyte. Relative to 100 weight percent of the sum of the polymer substrate and the ion conductive ceramic material, 1 weight percent to 30 weight percent of the polymer substrate is included; relative to 100 weight percent of the sum of the polymer substrate and the ion conductive ceramic material, 70 weight percent to 99 weight percent of the ion conductive ceramic material is included, The liquid electrolyte is contained in an amount of 5 to 40 parts by weight relative to 100 parts by weight of the composite of the ion conductive ceramic material and the polymer substrate, The polymer substrate of the first composite electrolyte layer is polyvinylidene fluoride or its copolymer, and the ion conductive ceramic material is an ion conductive ceramic material selected from phosphates, oxides, sulfides and mixtures thereof. The polymer substrate of the second composite electrolyte layer is polyvinylidene fluoride or its copolymer, and the ion conductive ceramic material is an oxide ion conductive ceramic material.

3. A double-layer composite electrolyte for a secondary battery, comprising: A first composite electrolyte layer disposed toward the positive electrode portion; A second composite electrolyte layer is provided facing the negative electrode portion, in, The first composite electrolyte layer and the second composite electrolyte layer include a polymer substrate, an ion conductive ceramic material and a liquid electrolyte. Relative to 100 weight percent of the sum of the polymer substrate and the ion conductive ceramic material, 1 weight percent to 30 weight percent of the polymer substrate is included; relative to 100 weight percent of the sum of the polymer substrate and the ion conductive ceramic material, 70 weight percent to 99 weight percent of the ion conductive ceramic material is included, The liquid electrolyte is contained in an amount of 5 to 40 parts by weight relative to 100 parts by weight of the composite of the ion conductive ceramic material and the polymer substrate, The polymer substrate of the first composite electrolyte layer is polyacrylonitrile or its copolymer, and the ion conductive ceramic material is an ion conductive ceramic material selected from phosphates, oxides, sulfides and mixtures thereof. The polymer substrate of the second composite electrolyte layer is polyacrylonitrile or its copolymer, and the ion conductive ceramic material is a sulfide ion conductive ceramic material.

4. The double-layer composite electrolyte for secondary batteries according to claim 1, wherein The ion conductive ceramic material of the first composite electrolyte layer is selected from Li 1+x Ti 2-x Al x (PO4)3(0 <x<2)、Li7La3Zr2O 12 , Li2S-P2S5 and ion conductive ceramic materials in their mixtures, The ion conductive ceramic material of the second composite electrolyte layer is Li 1+x Al x Ge 2-x (PO4)3(0 <x<2)。 5. The double-layer composite electrolyte for secondary batteries according to claim 2, wherein: The ion-conductive ceramic material of the first composite electrolyte layer is an ion-conductive ceramic material selected from Li 1+x Ti 2-x Al x (PO4)3 (0 < x < 2), (La, Li)TiO3, Li2S-P2S5, and mixtures thereof. The ion conductive ceramic material of the second composite electrolyte layer is selected from β-Al2O3, Li7La3Zr2O 12 And ion conductive ceramic materials in mixtures thereof.

6. The double-layer composite electrolyte for secondary battery according to claim 3, wherein: The ion conductive ceramic material of the first composite electrolyte layer is selected from Li 1+x Ti 2-x Al x (PO4)3(0 <x<2)、Li7La3Zr2O 12 , Li2S-P2S5 and ion conductive ceramic materials in their mixtures, The ion conductive ceramic material of the second composite electrolyte layer is selected from Li 3.25 Ge 0.25 P 0.75 Ion conductive ceramic materials among S4, Li2O-SiO2 and their mixtures.

7. The double-layer composite electrolyte for secondary batteries according to claim 1, wherein: The polymer substrate of the first composite electrolyte layer is polyvinylidene fluoride, and the ion-conductive ceramic material is Li 1+ x Ti 2-x Al x (PO4)3 (0 < x < 2). The polymer substrate of the second composite electrolyte layer is polyvinylidene fluoride, and the ion-conductive ceramic material is Li 1+x Al x Ge 2-x (PO4)3)(0 < x < 2).

8. The double-layer composite electrolyte for secondary batteries according to claim 1, wherein: The polymer substrate of the first composite electrolyte layer is polyvinylidene fluoride, and the ion conductive ceramic material is Li7La3Zr2O 12 The polymer substrate of the second composite electrolyte layer is polyvinylidene fluoride, and the ion conductive ceramic material is Li 1+x Al x Ge 2-x (PO4)3(0 <x<2)。 9. The double-layer composite electrolyte for secondary batteries according to claim 1, wherein: The polymer substrate of the first composite electrolyte layer is polyvinylidene fluoride, and the ion conductive ceramic material is Li2S-P2S5. The polymer substrate of the second composite electrolyte layer is polyvinylidene fluoride, and the ion conductive ceramic material is Li 1+ x Al x Ge 2-x (PO4)3(0 <x<2)。 10. The double-layer composite electrolyte for secondary batteries according to claim 2, wherein: The polymer substrate of the first composite electrolyte layer is polyvinylidene fluoride, and the ion-conductive ceramic material is Li 1+ x Ti 2-x Al x (PO4)3 (0 < x < 2). The polymer substrate of the second composite electrolyte layer is polyvinylidene fluoride-trifluoroethylene, and the ion-conductive ceramic material is β-Al2O3.

11. The double-layer composite electrolyte for secondary batteries according to claim 2, wherein: The polymer substrate of the first composite electrolyte layer is polyvinylidene fluoride, and the ion-conductive ceramic material is Li 1+ x Ti 2-x Al x (PO4)3 (0 < x < 2). The polymer substrate of the second composite electrolyte layer is polyvinylidene fluoride-trifluoroethylene, and the ion-conductive ceramic material is Li7La3Zr2O 12 .

12. The double-layer composite electrolyte for secondary batteries according to claim 2, wherein: The polymer matrix of the first composite electrolyte layer is polyvinylidene fluoride, and the ion conductive ceramic material is (La, Li)TiO3; the polymer matrix of the second composite electrolyte layer is polyvinylidene fluoride-trifluoroethylene, and the ion conductive ceramic material is β-Al2O3.

13. The double-layer composite electrolyte for secondary batteries according to claim 2, wherein: The polymer matrix of the first composite electrolyte layer is polyvinylidene fluoride, and the ion conductive ceramic material is Li2S-P2S5. The polymer matrix of the second composite electrolyte layer is polyvinylidene fluoride-trifluoroethylene, and the ion conductive ceramic material is β-Al2O3.

14. The double-layer composite electrolyte for secondary batteries according to claim 2, wherein: The polymer substrate of the first composite electrolyte layer is polyvinylidene fluoride, and the ion-conductive ceramic material is Li 1+ x Ti 2-x Al x (PO4)3 (0 < x < 2). The polymer substrate of the second composite electrolyte layer is polyvinylidene fluoride, and the ion-conductive ceramic material is Li7La3Zr2O 12 .

15. The double-layer composite electrolyte for secondary battery according to claim 3, wherein: The polymer substrate of the first composite electrolyte layer is polyacrylonitrile, and the ion-conductive ceramic material is Li 1+x Ti 2-x Al x (PO4)3 (0 < x < 2). The polymer substrate of the second composite electrolyte layer is polyacrylonitrile, and the ion-conductive ceramic material is Li 3.25 Ge 0.25 P 0.75 S4.

16. The double-layer composite electrolyte for secondary battery according to claim 3, wherein: The polymer substrate of the first composite electrolyte layer is polyacrylonitrile, and the ion conductive ceramic material is Li7La3Zr2O 12 The polymer substrate of the second composite electrolyte layer is polyacrylonitrile, and the ion conductive ceramic material is Li2O-SiO2.

17. The double-layer composite electrolyte for secondary battery according to claim 3, wherein: The polymer substrate of the first composite electrolyte layer is polyacrylonitrile, and the ion conductive ceramic material is Li2S-P2S5. The polymer substrate of the second composite electrolyte layer is polyacrylonitrile, and the ion conductive ceramic material is Li 3.25 Ge 0.25 P 0.75 S4.

18. The double-layer composite electrolyte for secondary battery according to claim 3, wherein: The polymer substrate of the first composite electrolyte layer is polyacrylonitrile, and the ion-conductive ceramic material is Li 1+x Ti 2-x Al x (PO4)3 (0 < x < 2). The polymer substrate of the second composite electrolyte layer is polyacrylonitrile, and the ion-conductive ceramic material is Li2O-SiO2.

19. A secondary battery comprising: A double-layer composite electrolyte for a secondary battery according to any one of claims 1 to 18.